Study on Thyroid Hormone Status in Case of Female Infertility - Tasnim, Nusrat; Begum, Rokeya (Anwer Khan Modern Medical College Journal, 2017)
Background: Infertility is a global health issue causing great personal sufferings and distress. It is also matter of social injustice and inequality. Both hyperthyroidism and hypothyroidism causes menstrual disturbances secondary to anovulation. The degree of disturbances varies from abnormal sexual development through menstrual irregularity to infertility. Objective: To assess thyroid hormone status in female infertility. Method: A cross-sectional study was carried out in the Department of Physiology, Dhaka Medical College, Dhaka during the period of July 2010 to June 2011. A total number of 250 female were included within the age limit of 20-40 years. Among them 125 subjects, healthy parous women were considered as control (group A) and 125 subjects, infertile women were considered as case (group B). The subjects were selected from Dhaka Medical College Hospital, infertility centre of BSMMU and BIRDEM, Dhaka. Data were collected in predesigned structured questionnaire form after taking consent. The study parameters are serumT3,T4 were measured in the Department of Nuclear Medicine, DMCH, Dhaka. For comparison between two groups, statistical analysis were done by Student's unpaired't' test. P<0.05 was considered as level of significance. Results: Serum T3 and T4 were significantly lower in group B than that of group A(P<0.001). Conclusion: From the results of the present study, it may be concluded that lower level of serum T3,T4 may be related with infertility. Anwer Khan Modern Medical College Journal Vol. 8, No. 2: Jul 2017, P 117-120